GEOCHEMISTRY AND GENESIS OF DEEP-SEATED ARCHEAN ENDERBITES IN THE SUTAM BLOCK, SOUTHERN ALDAN SHIELD - Mishkin M.A.; Vovna G.M.; Lavrik S.N.; Oktyabr'skii R.A. (My University, 2001)
The stratigraphic bottom of the deep-seated Sutam granulite complex is demonstrated to consist of a stratified metabasite-enderbite formation. Regularities in the distribution of major and trace elements indicate that the protoliths of these rocks were volcanics of the andesite-dacite and komatiite-basalt associations. The model proposed for the genesis of the volcanic associations includes two stages. Stage I involves decompressional partial melting of the material of an ascending mantle plume with the derivation of melts of the komatiite-basalt association. Stage II was marked by the production of volcanic rocks of the andesite-dacite association by the partial melting of the primary basaltic crust under the effect of heat provided by the ascending mantle plume. The protoliths of the metabasite-enderbite association of the Sutam block were produced at the boundary between the Early and Late Archean at 3.1 Ga.
Keywords: Aldan Shield; Sutam block; Archean; Precambrian::Archean; Докембрий::Архей